2017
DOI: 10.1016/j.sjopt.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of retinoblastoma in Alexandria: A step toward earlier diagnosis

Abstract: Objective: To evaluate the clinical presentation of retinoblastoma in Alexandria, Egypt, correlate the timing of accurate diagnosis with the presence of advanced disease and identify causes of delayed presentation. Methods: Retrospective noncomparative single institution study reviews demographic and clinical data of all new children with retinoblastoma presenting to Alexandria Main University ocular oncology clinic (OOC) from January 2012 to June 2014. Diagnosis time was from initial parental complaint to ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(31 reference statements)
2
6
0
2
Order By: Relevance
“…In the retinoblastoma cohort, delayed diagnosis longer than 2.5 months was an adverse prognostic factor, which is in agreement with the results of other studies [ 16 , 19 ]. Xiao et al [ 19 ] found that high-risk retinoblastoma had a longer interval from symptom presentation to enucleation than standard-risk retinoblastoma.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the retinoblastoma cohort, delayed diagnosis longer than 2.5 months was an adverse prognostic factor, which is in agreement with the results of other studies [ 16 , 19 ]. Xiao et al [ 19 ] found that high-risk retinoblastoma had a longer interval from symptom presentation to enucleation than standard-risk retinoblastoma.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings suggested that delayed diagnosis may affect the prognosis of pediatric retinoblastoma and neuroblastoma patients, inevitably leading to heavier economic and psychological burdens. Although the survivals of retinoblastoma and neuroblastoma have improved significantly, early diagnosis is still closely correlated with better prognosis, earlier disease stage, and smaller tumor size [ 16 ]. Pediatric solid tumors have unique anatomical locations, cellular origins, and clinical presentations [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a male predominance has been reported in some studies [ 13 ], which might be attributed to the lack of attention to female children in those countries, particularly in rural areas [ 13 ]. Similar to several prior studies [ 5 , 7 10 , 12 , 13 , 17 , 19 , 23 25 , 27 , 29 , 55 ], the most common presenting symptom in our study was leukocoria (76.5%), followed by strabismus (9.9%). As an initial sign, proptosis was found in 40% of cases in a study from Nepal [ 30 ], whereas none of our patients exhibited proptosis at their initial visit.…”
Section: Discussionsupporting
confidence: 90%
“…Another report from a single institute of Bangkok during 1997 to 2006, which included 90 retinoblastoma patients, showed the survival rate of 85% [ 6 ]. Numerous studies worldwide, including Asia [ 7 30 ] and Thailand [ 4 – 6 , 31 – 34 ], have described the clinical manifestations and treatment outcomes of retinoblastoma, but these studies did not use IAC, brachytherapy, or intravitreal chemotherapy as part of retinoblastoma treatment [ 5 8 , 11 13 , 17 19 , 23 25 , 30 – 34 ]. Therefore, our study was aimed to fill in the gap in investigating clinical presentations and treatment outcomes of retinoblastoma in relation to the advent of recent treatment modalities in Thailand.…”
Section: Introductionmentioning
confidence: 99%